ESTIMASI PENGUNJUNG MENGGUNAKANSIMULASI MONTE CARLO PADA WARUNG INTERNET XYZ - M. Haviz Irfani; Dafid Dafid (Jurnal Informatika Global)
Monte Carlo is a simulation method that using random numbers obtained from Linear Congruential Generator (multiplicative generator) as an approximation in estimating the number of visitors using previous time visitor data. The number of visitors who come to use internet services on internet cafes is often difficult to predict. Apart from some indicators that affect or may be experienced by the cafe owner with the activities of the internet service, it will  predicted the number of visitors using visitor data from 60 days ago with linear method congruential generator as scrambler and monte carlo method as estimator. The results obtained is the estimated number of visitor in uniform distribution [0,1] for the next 60 days that can be used as information for cafe owner.Keywords:Simulasi, Linier Congruential Generator, Monte Carlo, Estimasi, Random Number